(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper attempts to find out the relationship between the services provided by the OPD with the dimensions service quality service quality of the OPD. In other words, the impact of perceived quality of physical facilities, Physician services and technology based service encounters are being checked on the service quality where the dimensions of SERVQUAL have been studies.A data of 300 respondents were approached in the various OPDs situated in NCR of India wherein around 283 filled responses were being used for the data analysis. The data was collected from a well-drafted questionnaire developed considering the tested scales.It was found that all the hypotheses have been accepted and it can be pointed out that the physical facilities have a impact on the measurement of the service quality similarly the Physicians services also impact the service quality and further the newly added variable namely technology based services also has an impact on the dimensions of service quality.